2015
DOI: 10.1097/jom.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Lung Epithelium Injury in Occupational Hexavalent Chromium-Exposed Workers

Abstract: CC16, as an immunosuppressive protein, and CC16/SP-D can be used as sensitive and noninvasive biomarkers for lung injury. Smoking should be banned in chromium workplaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…As SP-D and CC-16 levels seem to reflect different mechanisms of lung damage, we decided to analyze the ratio between these two pneumoproteins ( 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…As SP-D and CC-16 levels seem to reflect different mechanisms of lung damage, we decided to analyze the ratio between these two pneumoproteins ( 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicate that circulating CC16 levels are decreased in lung injures caused by agents like tobacco or hexavalent chromium 20, 21. Chronic exposure to toxic agents causes a decline in the overall Clara cells located in terminal and respiratory bronchioles, leading to a relatively low production level of circulating CC16.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, CC16 levels may vary due to differences in sample collection, measurement time points, and methods used in different studies. For example, a previous study of chemical‐induced lung injury in rats has reported decreased serum CC16 levels after an initial transient increase compared to saline solution‐treated control animals 20. Some studies have also revealed that CC16 levels in bronchoalveolar fluid (BALF) differ from blood CC16 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither chest X-ray examination nor pulmonary function test is sensitive enough to perceive early health effects. These examinations could be modified by many confounding factors, especially noncompliance of workers and unprofessional determination [ 12 ]. Therefore, it is necessary to investigate proper biomarkers for lung injury among RCFs-exposed workers.…”
Section: Introductionmentioning
confidence: 99%